O drama satírico: gênero híbrido e intertextual - Vanessa Ribeiro Brandao (2012)
In this paper we discuss the satyr drama, a hybrid and intertextual Greek drama presented at theater contests in the Great Dionysias between V-II BC centuries. Its most outstanding feature that distinguishes it from other genres from its time is the presence of Silenus and his children, the satyrs, who form the chorus from the plays and are represented as creatures halfman half-animal (usually a goat with horse tail) with animal erect phallus. They are responsible for the humor and also for the sacredness of the genre because they are part of Dionysus cortege and present the god within the play. First we concerned about explainingsatyr dramas function and origin, then its distinctive features to the other genres. There are also some features which approximate satyr drama to these genres as the meter from the tragedy, the tone from the comedy, and rustic themes found in the Homeric hymns and collaborate to characterize it as a frontier genre, hybrid and intertextual.